Electrocatalytic hydrogen evolution reaction on reduced graphene oxide electrode decorated with cobaltphthalocyanine - Akyuz, Duygu; Keskin, Bahadir; Sahinturk, Utkan; Koca, Atif (ELSEVIER SCIENCE BV, 2016)
Electrocatalytic hydrogen evolution reaction (HER) on azido graphene oxide (GO-N-3) and reduced azido graphene oxide (RGO-N-3) electrodes decorated with the cobaltphthalocyanine complex bearing terminal alkyne moieties (TA-CoPc) was investigated. GCE/RGO-N-3 electrode was constructed with the electrochemical reduction of GO-N-3 coated on a glassy carbon electrode. Decoration of GCE/RGO-N-3 and GCE/GO-N-3 electrodes were performed with a new electrode modification technique, click electrochemistry (CEC), with which TA-CoPc complex was bonded to azido functional groups of GO-N-3 and RGO-N-3 on the electrodes. The modified GCE/RGO-N-3/TA-CoPc and GCE/GO-N-3/TA-CoPc electrodes were characterized with square wave voltammetry and electrochemical impedance spectroscopy (EIS), and then tested as heterogeneous electrocatalysts for HER. GCE/RGO-N-3/TA-CoPc electrode illustrates well electrocatalytic activity by decreasing the over-potential of the bare electrode about 340 mV and increasing the current density of the electrode about 15 fold at low pHs with absolutely high stability and reproducibility. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Electrocatalyst; Hydrogen evolution reaction; Phthalocyanine; Click electrochemistry; Graphene Oxide; Reduced graphene oxide; VERSATILE BUILDING-BLOCKS; OXYGEN REDUCTION; PERFORMANCE; FILMS; NANOPARTICLES; MEMBRANE; PHOTOCATALYSTS; NANOCOMPOSITES; Chemistry; Engineering